Filtering the desiri: The effects of time and space - Pérez González, Beatriz (Nómadas. Critical Journal of Social and Juridical Science, 2010)
After a previous analysis of the glances, words and gestures in seduction, the author now reflects on the effects of time and distance, the latter being understood as space. Time does not go by for seduction, or rather time produces seduction. Seduction is understood as a song with an allure akin to the sirens’ songs described by Ulysses.